Tried and Convicted: How Police, Prosecutors, and Judges Destroy Our Constitutional Rights - Cicchini, Michael D. (Rowman & Littlefield Publishers, 2012)
When an individual is accused of a crime he is provided, at least in theory, with numerous constitutional rights throughout the legal process. These constitutional rights, however, are soft and flexible, and are subject to a tremendous amount of manipulation by police, prosecutors, and judges. The result is that these government agents are easily able to bypass, and in fact destroy, our constitutional protections. This abuse of our fundamental rights is extremely dangerous. Far from being mere technicalities, constitutional rights benefit all citizens, not just the factually guilty, in ways that go unappreciated by most of us. In today’s hyper-vigilant, tough-on-crime climate, many good people from all walks of life find themselves charged with serious crimes for behaving in ways that most of us would be shocked to learn are criminal. For these reasons, it is in all of our interests to ensure strong constitutional safeguards for everyone. Tried and Convicted explains several individual constitutional rights that are intended to protect us from the vagaries of the criminal justice system, and gives detailed examples of how government agents routinely circumvent those rights. It also exposes the underlying problems that enable government agents to circumvent the constitution, and concludes by offering potential solutions to these problems. Using real life examples throughout, Cicchini provides a wake-up call for all of us.